The effect of different teaching styles to the puzzle completion of the Brgy. Airport Day Care Center pupils. - Pachoco, Jerilee
The study on The effects if the three teaching styles to the puzzle completion of the puzzle completion of the Barangay Airport Day Care Center pupils mainly aimed to determine if there is an effect on the three different teaching styles to the puzzle completion of the preschool children of the said preschool. There were a total number of 30 randomly selected participants, with 10 participants randomly assigned in each experimental conditions of supportive neutral and non-supportive. The experimental atudy used a multi-group or a 1 x 3 group design and the statistical used to analyzed results was the One-way analysis of variance (ANOVA), using time as the variable to measure the performance of the participants in solving the 9-piece jigsaw puzzles. Based on the statistical analysis, the results proved that the different teaching styles ahd no significant effect in the puzzle completion of the preschool students.